2014
DOI: 10.1016/j.rgg.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of the sedimentary-cover rocks of the West Siberian Plate in relation to their humidity and porosity

Abstract: We analyze the results of measurements of the thermal conductivity, porosity, and permeability of Mesozoic sedimentary rocks from wells drilled in the northeast of the West Siberian Plate and in the Cis-Yenisei basin. The thermal conductivity was measured by a “Thermal-conductivity comparator”, and the porosity and permeability were determined using standard techniques. A total of 135 samples of dry rocks were studied for thermal conductivity (λd). Ninety-two of them were then saturated with water, and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…They are usually in inverse correlation, which is stronger if the thermal conductivity and porosity are obtained from the same samples. The effect of the mineral composition of dry rocks on their thermal conductivity is minor (Duchkov et al, 2014). The thermal conductivity under the saturated condition is larger than the dry condition because the thermal conductivity of saline is higher than that of the air (Nabawy and Géraud, 2016).…”
Section: Influence Of Porosity Moisture and Fluid Content On Thermalmentioning
confidence: 97%
See 1 more Smart Citation
“…They are usually in inverse correlation, which is stronger if the thermal conductivity and porosity are obtained from the same samples. The effect of the mineral composition of dry rocks on their thermal conductivity is minor (Duchkov et al, 2014). The thermal conductivity under the saturated condition is larger than the dry condition because the thermal conductivity of saline is higher than that of the air (Nabawy and Géraud, 2016).…”
Section: Influence Of Porosity Moisture and Fluid Content On Thermalmentioning
confidence: 97%
“…research aimed at evaluating the rate of heat flow (Duchkov et al, 2014). As shown by numerous theoretical studies, the conductivity of rocks depends on various factors (such as, Yang et al, 1986;Liu et al, 2012;and Gao, 2015).…”
mentioning
confidence: 99%
“…He found that variation in temperature significantly affects the thermal diffusivity of rocks. In later years, several scholars [51][52][53][54][55][56][57] studied the effect of density, rock texture, permeability, fluid saturation, mineral composition and porosity of rocks on thermal conductivity. For instance, Barry-Macaulay et al [54] reported the variation in TC of soils and rocks with the variation in density.…”
Section: Thermal Conductivity and Petrophysical Parametersmentioning
confidence: 99%
“…For instance, Barry-Macaulay et al [54] reported the variation in TC of soils and rocks with the variation in density. Duchkov et al [55] revealed a stable linear relationship between the thermal conductivity of the dry samples of Mesozoic sedimentary rocks and, porosity and permeability. Haffen et al [58] studied the correlation of TC and porosity maps for granite and sandstone.…”
Section: Thermal Conductivity and Petrophysical Parametersmentioning
confidence: 99%
“…Selanjutnya batuan yang telah bersih dari lumut dan tanah tersebut di furnace dengan variasi temperatur 100 0 C, 200 0 C dan 300 0 C selama 1 jam tiap temperatur yang diberikan. Kemudian batuan yang telah di furnaceakan dilakukan pengukuran sifat fisis (Densitas dan porositas) batuan [6].…”
Section: Preparasi Sample Preparasi Sample Sifat Fisisunclassified